2009
DOI: 10.1128/jb.01416-08
|View full text |Cite
|
Sign up to set email alerts
|

The Complete Genome Sequence ofHelicobacter pyloriStrain G27

Abstract: Helicobacter pylori is a gram-negative pathogen that colonizes the stomachs of over half the world's population and causes a spectrum of gastric diseases including gastritis, ulcers, and gastric carcinoma. The H. pylori species exhibits unusually high levels of genetic variation between strains. Here we announce the complete genome sequence of H. pylori strain G27, which has been used extensively in H. pylori research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
169
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 185 publications
(171 citation statements)
references
References 14 publications
2
169
0
Order By: Relevance
“…We utilized the numerous previous transcriptional and proteomic studies regarding H. pylori Fur regulation (7,8,23,(32)(33)(34) to identify potential uncharacterized apo-Fur-repressed gene targets. Analysis of those studies showed considerable variability; thus, we imposed the following criteria to narrow the list of genes for study: (I) changes in expression (mRNA or protein) were consistent with apo Fur regulation (i.e., a Fur-dependent decrease in expression in the WT background upon iron chelation); (ii) the genes were present in strains G27 (35), 26695 (13), J99 (36), and HPAG1 (37), which are each well-characterized H. pylori strains; (iii) the genes did not appear to be essential (38); and (iv) the changes in expression exhibited in response to iron chelation and/or fur deletion were substantial (defined as a minimum 2-fold change). Based on these criteria, the cytochrome c 553 gene (HP1227) (23), hydA (HP0631) (7,23,32,34), and serB (HP0652) (23,32,33) were chosen for further study.…”
Section: Resultsmentioning
confidence: 99%
“…We utilized the numerous previous transcriptional and proteomic studies regarding H. pylori Fur regulation (7,8,23,(32)(33)(34) to identify potential uncharacterized apo-Fur-repressed gene targets. Analysis of those studies showed considerable variability; thus, we imposed the following criteria to narrow the list of genes for study: (I) changes in expression (mRNA or protein) were consistent with apo Fur regulation (i.e., a Fur-dependent decrease in expression in the WT background upon iron chelation); (ii) the genes were present in strains G27 (35), 26695 (13), J99 (36), and HPAG1 (37), which are each well-characterized H. pylori strains; (iii) the genes did not appear to be essential (38); and (iv) the changes in expression exhibited in response to iron chelation and/or fur deletion were substantial (defined as a minimum 2-fold change). Based on these criteria, the cytochrome c 553 gene (HP1227) (23), hydA (HP0631) (7,23,32,34), and serB (HP0652) (23,32,33) were chosen for further study.…”
Section: Resultsmentioning
confidence: 99%
“…In the final step, the upstream Kan r PCR product was fused the 5= end of the arsR construct by SOE PCR using Up1F and Dn4R. The resulting SOE PCR product was used to transform G27 (DSM1) (51). Transformants were selected on 25 g/ml Kan. Dn1F and Dn4R primers were used to PCR amplify Kan-resistant colonies, and the resulting amplicons were screened by restriction digestion with Apo1; the G¡A transition introduces an Apo1 site.…”
Section: Methodsmentioning
confidence: 99%
“…The strains of H. pylori used in this study included the sequenced strains 26695 (26), J99 (27), and G27 (28), as well as a babA knockout mutant of G27, strain G27⌬babA (a gift from Steffen Backert). H. pylori was routinely cultured at 37°C on Columbia blood agar base (Oxoid) containing 7% (vol/vol) defibrinated horse blood under microaerophilic conditions generated using CampyGen gas packs (Oxoid).…”
Section: Methodsmentioning
confidence: 99%